Mukhtar Yahya and the Method of Teaching Arabic: Analysis of Muhadasah Method in the Perspective of Behaviorism Theory - Mujahid, Mujahid (Jurnal Pendidikan Islam, 2018)
This research aims to explore Mukhtar Yahya and his thoughts on the Muhadasah method in learning Arabic which was analyzed by the learning theory of behaviorism. This is qualitative research with historical and psychological approaches. The historical approach is used since Mukhtar Yahya as the figure had passed away. While the psychological approach is used to analyze Muktar Yahya’s Muhadasah method. The results show first, Mukhtar Yahya was a figure who had a big role in the birth of PTAIN and IAIN Sunan Kalijaga. During his role in PTAIN and IAIN Sunan Kalijaga, Mukhtar Yahya held important positions, even Mukhtar Yahya often had double positions in IAIN. In his academic career, Mukhtar Yahya was a highly qualified intellectual in the fields of religion and the Arabic language. His ability was influenced by his intellectual brilliance and accompanied by a high spirit in studying religion. Second, the psychological approach shows that the Muhadasah method of Mukhtar Yahya was strongly influenced by behaviorism learning theory. Although Mukhtar Yahya did not say that his methods were influenced by behaviorism learning theory, the theory was highly visible in the learning steps of Muhadasah. In the Muhadasah method, the learning process will occur due to the presence of stimulus which then produces learning responses from students.